Cross β Amyloid Nanotubes Demonstrate Promiscuous Catalysis in a Chemical Reaction Network via Co‐option. Issue 48 (25th October 2022) - Roy, Soumili; Chatterjee, Ayan; Bal, Subhajit; Das, Dibyendu
Abstract: In Darwin's warm pond rich with nutrients, lesser number of early catalytic machineries with modest capabilities were able to demonstrate promiscuity by catalyzing diverse biochemical transformations important for protometabolism. Herein, we report catalytically promiscuous amyloid‐based short peptide assemblies that could concomitantly catalyse three metabolically important yet orthogonal reactions. The surface exposed catalytic dyads featuring lysines and imidazoles were utilized for C=N condensation via dynamic covalent linkages and modulation of protonation events, respectively. Further, the peptide assemblies could promiscuously catalyse hydrolysis as well as retro‐aldol reactions, that could be co‐opted to facilitate C=N bond formation, either by a feedforward‐driven reaction network or by replenishing depleted substrates. The catalytic diversity of short peptide based promiscuous β‐sheet folds suggests their possible role in promoting the protometabolic network in early earth. Abstract : The promiscuous competencies of cross β nanotubes were shown towards a reaction network with three orthogonal transformations that are connected via co‐option, underpinning the important roles of short amyloids as earliest enzymatic folds.